A Persistent and Intense Marine Heatwave in the Northeast Pacific During 2019–2020. Issue 13 (2nd July 2021) - Chen, Ziyan; Shi, Jian; Liu, Qinyu; Chen, Hui; Li, Chun
Abstract: Motivated by increasing marine heatwaves (MHWs) and their dramatic climate effects, we analyze the persistent 2019–2020 MHW, which showed significant positive sea surface temperature (SST) anomalies in the Northeast Pacific. Four SST peaks were identified during its evolution, which appeared in November 2019, April, July, and November 2020. Positive temperature anomalies were mostly located within the mixed layer for the first‐year winter peak. However, the warm core was centered around 50 m below (at the bottom of) the mixed layer for the summer (second‐year winter) peak. The dominant factor for the two wintertime peaks was a surface heat flux anomaly, with reduction in evaporative cooling due to the easterly anomaly. The heat flux and potentially the vertical entrainment combined to induce the peak in spring. In the tropical Pacific, a La Niña event occurred following this MHW, while other recorded double‐peak events were associated with El Niño or neutral conditions. Plain Language Summary: With an increasing focus on marine heatwaves (MHWs) and their dramatic climate effects, we analyze the most recent event during 2019–2020, which showed significant positive sea surface temperature (SST) anomalies in the Northeast Pacific. Four peaks in SST intensity were identified in November 2019, April, July, and November 2020. The prominent easterly anomalies counteracting against the climatological westerlies led to smaller latent heat loss, which primarily contributed to the warming of the two wintertime peaks. Heat budget analysis revealed that the surface heat flux and potentially the vertical entrainment combined to induce the warming peak in spring. In the tropical Pacific, a La Niña event occurred following this MHW, while other recorded double‐peak events were associated with El Niño or neutral conditions. Key Points: Sea surface temperature anomalies during the 2019–2020 Northeast Pacific marine heatwave had four peaks with one in boreal spring of 2020 Anomalous heat flux was the primary factor responsible for both wintertime peaks Different from past marine heatwaves, a La Niña event occurred in tropical Pacific during the late stage of the 2019–2020 marine heatwave